PENGARUH PEMBERIAN JUS SEMANGKA MERAH DAN JUS SEMANGKA KUNING TERHADAP TEKANAN DARAH PADA TEKANAN DARAH TINGGI DI DESA SUKANAGARA KABUPATEN TANGERANG TAHUN 2020 - Nesa Nesa Ria Octaviani; Bella Novita A.S (Nusantara Hasana Journal, 2021)
Hypertension or can be called high blood pressure is a condition where a person experiences an increase in abnormal blood pressure. Objective: to determine the effect of giving red watermelon juice and yellow watermelon juice to a decrease in blood pressure. Method: This study used a quasi-experimental design of two groups pre-test post-test without control group. The analysis test used is Shapiro Wilk. The selection of research subjects using the purpose sampling method. Data analysis was performed by paired sample T-Test. Results: The results of the study the administration of red watermelon juice and yellow watermelon juice (p = 0,000 <0.05). Giving watermelon red juice is effective in reducing average systolic blood pressure (pretest) 154.00 mm / Hg to systolic (posttest) 146.00 mm / Hg, diastolic (posttest) 94.00 mm / Hg as well as giving watermelon juice effectively reducing average blood pressure systolic (pretest) 168.00 mm / Hg, diastoic (pretest) 117.00 mm / Hg as well as systolic average (posttest) 152.00 mm / Hg and (posttest) 91.00 mm / Hg. Conclusion: Giving watermelon red and yellow watermelon juice with hypertension is effective for lowering blood pressure.